Linking Nurses' Perceptions of Patient Care Quality to Job Satisfaction: The Role of Authentic Leadership and Empowering Professional Practice Environments. (May 2015) - Spence Laschinger, Heather K.; Fida, Roberta
Abstract : OBJECTIVES: A model linking authentic leadership, structural empowerment, and supportive professional practice environments to nurses' perceptions of patient care quality and job satisfaction was tested. BACKGROUND: Positive work environment characteristics are important for nurses' perceptions of patient care quality and job satisfaction (significant factors for retention). Few studies have examined the mechanism by which these characteristics operate to influence perceptions of patient care quality or job satisfaction. METHODS: A cross-sectional provincial survey of 723 Canadian nurses was used to test the hypothesized models using structural equation modeling. RESULTS: The model was an acceptable fit and all paths were significant. Authentic leadership had a positive effect on structural empowerment, which had a positive effect on perceived support for professional practice and a negative effect on nurses' perceptions that inadequate unit staffing prevented them from providing high-quality patient care. These workplace conditions predicted job satisfaction. CONCLUSION: Authentic leaders play an important role in creating empowering professional practice environments that foster high-quality care and job satisfaction.